Unveiling a cutting-edge bi-ligand nickel metal-organic framework as an electrode material for symmetric supercapacitors - Kale, Amol M.; Biradar, Madan R.; Cho, Won-Je; Kaya, Cengiz; Bhosale, Sheshanath V.; Bhosale, Sidhanath V.; Kim, Byung Chul (ELSEVIER, 2023)
Perylene diimide (PDI)-based MOFs feature a substantial specific capacitance, terrific cycle durability, swift charge/discharge rates, exceptional chemical as well as thermal endurance, diversity in electrode design, and inexpensive production costs. In light of these benefits, PDI-based MOFs are intriguing options for utilization in energy storage. Inspired by the distinctive features of perylene diimide-based ligands, highly conjugated and nitrogen-rich organic ligands Perylene diimide-L-dopa (PDI-L-Dopa) were incorporated to create the Ni-MOF architecture. The resulting hierarchical flower-like microspheres of bi-ligand Ni-MOF had better electron transport, conductivity, and wettability. When applied as electrode material in a three-electrode system considering a specific capacitance of 198 F/g at a current density of 1 A/g, the Ni-MOF-24 h electrode showcased beneficial electrochemical efficiency. XRD, FT-IR, and XPS were used to validate the formation of Ni-MOF and disclose the exact chemical composition and valence state inside the material. The hierarchical flower-like microsphere structure of the Ni-MOF, formed of 2D petal-like nanosheets, was revealed by FE-SEM and TEM. Additionally, when Ni-MOF-24 h electrodes used to fabricate symmetric supercapacitor (SSC), it reveals a high energy density (Ed) of 23 Wh/kg at a corresponding power density (Pd) of 600 W/kg along with extraordinary cyclic stability over 10,000 charge/discharge cycles with retaining 99 % of the initial capacitance. This research sheds light on the design and manufacture of innovative materials for long-term and efficient energy storage devices based on MOFs.
Keywords: Ni-MOF; Novel ligand; PDI-L-Dopa; Symmetric supercapacitors; Long cyclic durability; PSEUDO-CAPACITIVE MATERIAL; ENERGY; COMPOSITES; FABRICATION; DESIGN; Energy & Fuels